2022
DOI: 10.1111/jvim.16578
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization of epileptic seizures in Pomeranians with idiopathic epilepsy or epilepsy of unknown cause

Abstract: Background Focal epileptic motor seizures manifested by limb contraction have been recognized anecdotally in Pomeranians. Objectives To investigate clinical features of idiopathic epilepsy (IE) and epilepsy of unknown cause (EUC) in Pomeranians as well as the ADAM23 haplotype frequency previously reported as a common risk haplotype for epilepsy in several breeds of dogs. Animals Twenty‐eight Pomeranians, including 15 with IE and 13 with EUC. Nine Pomeranians with epilepsy and 8 control Pomeranians were used fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
2
0
5
Order By: Relevance
“…For example, paroxysmal dyskinesia sometimes mimic focal epileptic seizures [ 32 ]. The importance of finding interictal EDs to distinguish between paroxysmal dyskinesia and focal epileptic seizures was recently reported in Pomeranians [ 33 ]. Bemegride may be used to help to make a diagnosis of epilepsy based on the dose required to activate EDs, especially in situations where a strict diagnosis is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, paroxysmal dyskinesia sometimes mimic focal epileptic seizures [ 32 ]. The importance of finding interictal EDs to distinguish between paroxysmal dyskinesia and focal epileptic seizures was recently reported in Pomeranians [ 33 ]. Bemegride may be used to help to make a diagnosis of epilepsy based on the dose required to activate EDs, especially in situations where a strict diagnosis is required.…”
Section: Discussionmentioning
confidence: 99%
“…It is observed in hypoxic encephalopathy and other brain dysfunctions or during deep anesthesia. A previous study showed that the burst activities of BS included spikes and sharp waves in dogs regardless of whether the dog had epilepsy, similar to humans [ 33 ]. To unify the depth of anesthesia, the concentration of sevoflurane was maintained at the point at which BS had just completely disappeared from the EEG trace in all dogs.…”
Section: Discussionmentioning
confidence: 99%
“…Existen puntos de contacto con la epilepsia focal motora del Pomerania (Yu et al, 2022). La mayoría de los Caniches presentaron CFM solamente (88%), y permanecieron en alerta durante las crisis (94%).…”
Section: Semiología De Las Crisisunclassified
“…En 71% de los casos las DEIs fueron contralaterales al lado donde ocurría el inicio de la CFM; en el resto se observaron en ambos hemisferios cerebrales. Estos hallazgos fueron similares a los comunicados en la epilepsia focal motora del Pomerania (Yu et al, 2022). Las localizaciones de las DEIs en algunos perros no coincidieron con la región sugerida por la semiología de las crisis.…”
Section: Análisis Del Eegunclassified
See 1 more Smart Citation